2011
DOI: 10.1111/j.1365-3156.2011.02776.x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of stillbirth, neonatal death and early childhood death in rural Zambia by verbal autopsy assessments

Abstract: Summary OBJECTIVES To describe specific causes of the high rates of stillbirth, neonatal death and early child childhood death in Zambia. METHODS We conducted a household-based survey in rural Zambia. Socio-demographic and delivery characteristics were recorded, alongside a maternal HIV test. Verbal autopsy questionnaires were administered to elicit mortality-related information and independently reviewed by three experienced paediatricians who assigned a cause and contributing factor to death. For this sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
5
18
1
4
Order By: Relevance
“…20,21 By contrast, 63% of all stillbirths in our cohort likely occurred during labor or near the time of delivery. This estimate is similar to that from a recent study from rural Zambia, which showed a rate of 72% of non-macerated stillbirths, 22 and a multi-country study from the Global Network, which reported that 67% of all stillbirths in Zambia were non-macerated, suggesting an intrapartum stillbirth. 20 In our cohort of women with a prior CD, intrapartum stillbirths were more likely to occur than antepartum stillbirths.…”
Section: Discussionsupporting
confidence: 88%
“…20,21 By contrast, 63% of all stillbirths in our cohort likely occurred during labor or near the time of delivery. This estimate is similar to that from a recent study from rural Zambia, which showed a rate of 72% of non-macerated stillbirths, 22 and a multi-country study from the Global Network, which reported that 67% of all stillbirths in Zambia were non-macerated, suggesting an intrapartum stillbirth. 20 In our cohort of women with a prior CD, intrapartum stillbirths were more likely to occur than antepartum stillbirths.…”
Section: Discussionsupporting
confidence: 88%
“…This study has identified preterm birth (19.4%) as the second cause of neonatal death. Sombie [18] in the West of Burkina Faso, Edmond et al [13] in Ghana, and Turnbull et al [12] in Zambia had made the same observation, with the respective preterm death rates of 15%, 19.7%, and 34%. Poverty, hardship of field work and chores, the long walks on foot to look for firewood and water are situations experienced daily by women in the area of this study, which encourage preterm deliveries.…”
Section: Neonatal Deathsmentioning
confidence: 70%
“…The percentage attribution ranged from 8 to 50% of stillbirths. Maternal conditions as causes of stillbirth such as diabetes, HIV, syphilis and hypertensive disorders were the most commonly reported …”
Section: Resultsmentioning
confidence: 99%